The effect of mind mapping on the level of student learning success in the Pancasila course: a study on students of the UNY English department - Nurhanifah, Isra'; Murdiono, Mukhamad; Puspitasari, Chandra Dewi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The quality of a nation's human resources can be measured from the learning achievements of students. Learning achievement is an indicator of student learning success and also an indicator of educator success in conducting learning. Learning success reflects the success of students in mastering learning concepts expressed by grades. One way to increase student understanding of concepts is by applying mind mapping. This study aims to determine the effect of mind mapping on the success rate of student learning in the Pancasila course. The method used in this research is Pre-Experimental with One Group Pretest-Posttest Design. The research sample consisted of 36 students majoring in English literature at UNY by choosing purposive sampling. Analysis of the learning outcomes obtained shows that the value of ha is accepted which means that the effect of applying mind mapping has on student learning success in the Pancasila course. While the Gain value (the average increase as an indicator of learning success) obtained results of 0.33 in the medium category. The implication of this research is as a source of information or a reference for educators that the application of mind mapping in learning can increase learning success.